The population of Japan. - Taeuber, Irene Barnes (Princeton, Princeton University Press, 1958)
This study begins with the demography of the legendary period and proceeds swiftly through the twelve centuries of recorded history from the Great Reform of 650 A.D. to the Meiji Restoration of 1868.
"[Prepared] under the editorial sponsorrship of Office of Population Research, Princeton University."
Bibliography: p. [395]-455.
osc 5/11/2021
Loans
Keywords: Japan